Effects of zinc porphyrin and zinc phthalocyanine derivatives in photodynamic anticancer therapy under different partial pressures of oxygen in vitro - Pola, Martin; Kolarova, Hana; Ruzicka, Jiri; Zholobenko, Aleksey; Modriansky, Martin; Mosinger, Jiri; Bajgar, Robert (Investigational new drugs, 2021)
Photodynamic therapy (PDT) is gradually becoming an alternative method in the treatment of several diseases. Here, we investigated the role of oxygen in photodynamically treated cervical cancer cells (HeLa). The effect of PDT on HeLa cells was assessed by exposing cultured cells to disulphonated zinc phthalocyanine (ZnPcS2) and tetrasulphonated zinc tetraphenylporphyrin (ZnTPPS4). Fluorescence microscopy revealed their different localizations within the cells. ZnTPPS4 seems to be mostly limited to the cytosol and lysosomes, whereas ZnPcS2 is most likely predominantly attached to membrane structures, including plasmalemma and the mitochondrial membrane. Phototoxicity assays of PDT-treated cells carried out under different partial pressures of oxygen showed dose-dependent responses. Interestingly, ZnPcS2 was also photodynamically effective at a minimal level of oxygen, under a nitrogen atmosphere. On the other hand, hyperbaric oxygenation did not lead to a higher PDT efficiency of either photosensitizer. Although both photosensitizers can induce a significant drop in mitochondrial membrane potential, ZnPcS2 has a markedly higher effect on mitochondrial respiration that was completely blocked after two short light cycles. In conclusion, our observations suggest that PDT can be effective even in hypoxic conditions if a suitable sensitizer is chosen, such as ZnPcS2, which can inhibit mitochondrial respiration.
Keywords: parciální tlak; Photodynamic therapy; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; organokovové sloučeniny; Indoles; Partial Pressure; mitochondrie; Photosensitizing Agents; fotosenzibilizující látky; HeLa Cells; Singlet Oxygen; fotochemoterapie; membránový potenciál mitochondrií; metaloporfyriny; kyslík; Humans; Organometallic Compounds; Photochemotherapy; Hyperbaria; viabilita buněk; Cell Survival; Photosensitizers; Mitochondria; indoly; Metalloporphyrins; Oxygen; Membrane Potential, Mitochondrial; singletový kyslík; HeLa buňky; lidé